Sosialisasi kawasan keselamatan operasi penerbangan di Desa Durian Kecamatan Pantai Labu Kabupaten Deli Serdang - Hairul Amren Samosir; Panangian Mahadi Sihombing; Muhammad Amril (LPPM Universitas Al-Azhar medan, 2024)
Rules related to aviation operation safety areas (KKOP) authorized by the International Civil Aviation Organization (ICAO) must be complied with. The regulations related to the KKOP must involve the community and related government employees to be implemented optimally. This is done to avoid the cause of aircraft accidents in the airport flight area. Therefore, awareness activities related to KKOP rules need to be carried out to the community and relevant local government employees. KKOP socialization in Durian Village which is directly adjacent to Kualanamu International Airport in Deli Serdang has been carried out by Medan Aviation Polytechnic lecturers through community service programs. The airport was chosen because it is the fourth largest airport with an area of 1,650 ha and is among the top 10 busiest airports in Indonesia. KKOP socialization materials include descriptions related to community activities that are contrary to KKOP rules. In addition, the elaboration of binding legal aspects related to KKOP was also conveyed in socialization activities. Thus, the rules related to KKOP are expected to be obeyed by the community around the airport. Topics related to the rights of the community around KKOP were also presented to the community.